Early application of awake extracorporeal membrane oxygenation in pneumocystis jirovecii pneumonia complicated with severe acute respiratory distress syndrome: a case report - Wu, Qinglin; Cen, Fulan; Wang, Guowei; Huang, Jia (Frontiers in Medicine, 2023)
Introduction: Generally, patients suffering from severe acute respiratory distress syndrome (ARDS) have typically been treated with mechanical ventilation. The use of extracorporeal membrane oxygenation (ECMO) has traditionally been considered a life-saving therapy, reserved as a last resort when other treatment options have been exhausted. This report details our successful initial experience with the early implementation of awake venovenous extracorporeal membrane oxygenation (VV-ECMO) in a case of pneumocystis jirovecii pneumonia complicated with severe acute respiratory distress syndrome (ARDS), offering a promising new approach to recovery.We report successful use of awake VV-ECMO in a 29-year-old man who manifested with severe ARDS, caused by pneumocystis jirovecii pneumonia. The patient initially received treatment with antibiotic treatment and non-invasive ventilation (NIV) for respiratory distress, but these interventions failed to improve the patient's dyspnea, which was worsening. Following a treatment approach involving combined antifungal therapy, high-flow nasal cannula oxygen therapy (HFNC), and VV-ECMO for a duration of 7 days, the patient's symptoms improved and showed relief.